A young female with pulmonary sarcoidosis masquerading as bronchial asthma - Rahman, Mohammed Mirazur; Habib, Farjana Binte; Kabir, Ahmed Imran; Khaled, Shaifuddin Mohammad; Rahman, Samia; Jahan, Rawnak (BIRDEM Medical Journal, 2026)
Sarcoidosis is a multisystem granulomatous disorder that commonly affects the lungs. Accumulation of nonnecrotizing granulomas and subsequently fibrosis in the lungs and other organs accounts for the clinical manifestations. A young female patient complaining of shortness of breath, cough and wheezing. First she was treated as asthma for long time and there was no improvement. Then a computed tomography of chest was performed and fine needle aspiration from hilar lymphnode confirmed pulmonary sarcoidosis. She received corticosteroid therapy for six months and her health situation become well. BIRDEM Med J 2026; 16(1): 33-35